2021
DOI: 10.1186/s12974-021-02117-y
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological ablation of astrocytes reduces Aβ degradation and synaptic connectivity in an ex vivo model of Alzheimer’s disease

Abstract: Background Astrocytes provide a vital support to neurons in normal and pathological conditions. In Alzheimer’s disease (AD) brains, reactive astrocytes have been found surrounding amyloid plaques, forming an astrocytic scar. However, their role and potential mechanisms whereby they affect neuroinflammation, amyloid pathology, and synaptic density in AD remain unclear. Methods To explore the role of astrocytes on Aβ pathology and neuroinflammatory m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…Based on the electrophysiological and behavioral experiments, and on the immunohistochemistry results, it is concluded that relatively mild stress may cause MDD-like behavior in rodents by activating microglial P2X7Rs, while in the case of more pronounced stress, astrocytic P2X7Rs also become involved. This was directly confirmed-in agree-ment with the electrophysiology data-by the use of mice pretreated with the selective astrocytic toxin L-α-aminoadipate [69,70] or with minocycline [71], a selective inhibitor of microglial activation.…”
Section: Discussionsupporting
confidence: 65%
“…Based on the electrophysiological and behavioral experiments, and on the immunohistochemistry results, it is concluded that relatively mild stress may cause MDD-like behavior in rodents by activating microglial P2X7Rs, while in the case of more pronounced stress, astrocytic P2X7Rs also become involved. This was directly confirmed-in agree-ment with the electrophysiology data-by the use of mice pretreated with the selective astrocytic toxin L-α-aminoadipate [69,70] or with minocycline [71], a selective inhibitor of microglial activation.…”
Section: Discussionsupporting
confidence: 65%
“…Although this might suggest that the presence of astrocytes in AD is harmful and that removing them could have therapeutic effects, we have to be careful. For example, when pharmacologically ablating astrocytes in organotypic brain slices from 5xFAD mice, Aβ levels increased and spine density and size were reduced (Davis et al, 2021 ). A better treatment option might be to specifically target reactive astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, crosstalk between astrocytes and microglia in the hippocampus is responsible for sensitivity to insults ( Lana et al, 2020 ), pointing to the importance of communication between astroglia and brain-resident macrophages in cognitive dysfunctions ( Liddelow et al, 2017 ; Linnerbauer et al, 2020 ). Furthermore, astrocytes and microglia participate in Aβ clearance and protection of synaptic connectivity in AD models, suggesting highly context-dependent immunological roles of these glial cell populations against AD development ( Davis et al, 2021 ).…”
Section: Metabolic Disturbance and Cognitive Impairmentmentioning
confidence: 99%